2020
DOI: 10.5755/j01.ee.31.3.25158
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Public Health Expenditure on Health Component of Human Capital

Abstract: The analysis of the concept of human capital shows that this form of capital includes a set of different components that are used in economic activities and generates different kind of benefits. Health is one of the main components of human capital. Hence, considering its importance authors of this article tried to investigate the impact of public health expenditure on the health component of human capital. Ordinary least square, fixed and random effects panel data models for 28 European Union countries were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
(64 reference statements)
1
5
0
1
Order By: Relevance
“…However, the coefficient of greenhouse shows a positive connection with health expenditures consistent with the outcomes ( 26 ). The positive associations between HC and health expenditure in the long-run estimation results are in line with those of ( 47 ). Although the rest is attributable to the novelty of the variables, there is no such study associated with the present findings that explain the causal and long-run relationships.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, the coefficient of greenhouse shows a positive connection with health expenditures consistent with the outcomes ( 26 ). The positive associations between HC and health expenditure in the long-run estimation results are in line with those of ( 47 ). Although the rest is attributable to the novelty of the variables, there is no such study associated with the present findings that explain the causal and long-run relationships.…”
Section: Discussionsupporting
confidence: 88%
“…Health is one of the components of HC that are prerequisites for economic development ( 46 ) quality of health is substantially essential and positive for productivity and economic progress ( 47 ) demonstrated in the findings that improvement in health expenditures significantly enhances the HC of the country ( 48 ) investigated HC in improving substantial impact on productivity and growth ( 49 ) observed that HC directly or indirectly affects the economic growth of the country ( 50 ) also examined the association between HC, economic growth, and health expenditures in the case of developing economies. The results depicted that health expenses and economic growth are substantially associated with HC.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Augmenting investment in people's well-being is pivotal for enhancing service quality in the post-COVID-19 era. The allocations for people's welfare markedly influence human capital development [22], labor productivity, and regional innovation dynamism, consequently propelling regional high-quality development. According to endogenous growth theory, technological advancements serve as the driving force behind continual economic progress.…”
Section: Theoretical Analysis and Research Hypothesismentioning
confidence: 99%
“…Gavurova et al (2020) identified a population index, an intensive care unit transfer rate, a long-term hospitalization rate, a mortality rate, and a mortality rate from surgery as indicators of the medical sector quality and the impact on patient satisfaction. Railaite & Čiutienė (2020) believe that healthcare costs have the greatest impact on the health component of human capital and, consequently, on the country's health as a whole. Chen & Sun (2021) investigate the health of business ecosystems and identify such determinants as the dominant capabilities of the enterprise platform, the potential for collaboration of an additional enterprise, products and services, the sector environment.…”
Section: Literature Reviewmentioning
confidence: 99%